Human-robot interaction with bionic arm experimental setup for robotics education - (:unkn) unknown (KAUNAS UNIV TECHNOLOGY PRESS, 2008)
In this study an interactive human-robot bionic arm has been designed. Designed interactive human-robot bionic arm has been converted into experiment setup to teach forward and inverse kinematics as applied for mechatronics student. To manufacture the body of the systems a plaster is moulded around a real human arm. The interacting system includes two in-dependent robotic arms; one for motion capture and the other for manipulation purposes. The motion capture system includes a wearable device to obtain the motion data from human arm. The manipulator system includes a robotic arm which generates the motion specified by the data obtained from the capturing system.
Keywords: human-robot interaction; robotic arm; robotic education